ANALYSIS OF THE WELFARE LEVEL OF LEBAK SWAMP RICE FARMERS AT A CROPPING INDEX (IP) OF 100 AND IP OF 200 IN GELEBAK DALAM VILLAGE RAMBUTAN DISTRICT BANYUASIN REGENCY - Felyn Muharani; Indri Januarti (Journal Informatic, Education and Management (JIEM), 2026)
The swamp land in Banyuasin Regency, especially in Gelebak Dalam Village, Rambutan District, has great potential for rice farming development but its utilization has not been optimal. The government has implemented a program to increase the Cropping Index (IP) from 100 to 200 to improve land productivity and farmer welfare. The objectives of this study are (1) To calculate the income of swamp rice farming businesses with IP 100 and IP 200 in Gelebak Dalam Village, Rambutan District, Banyuasin Regency, (2) To calculate the contribution of rice farming income to the total household income of swamp rice farmers with IP 100 and IP 200 in Gelebak Dalam Village, Rambutan District, Banyuasin Regency, and (3) To compare the welfare levels of swamp rice farmers with IP 100 and IP 200 in Gelebak Dalam Village, Rambutan District, Banyuasin Regency. This research was conducted in Gelebak Dalam Village, Rambutan District, Banyuasin Regency in November 2025. The research method used was a survey method with a quantitative descriptive approach and a sampling method using disproportionate stratified random sampling. The data used were primary data obtained through structured interviews and secondary data from related agencies. The results of this study are (1) The income of IP 100 rice farming business was IDR4,210,393/month or IDR50,524,716/year, while IP 200 was IDR7,925,852/month or IDR91,885,282/year. The total household income of IP 100 farmers reached IDR5,999,560/month or IDR71,994,720/year, while IP 200 reached IDR9,153,185/month or IDR130,853,282/year, (2) The contribution of rice farming income to household income for IP 100 farmers was 70.17% (dominant) and IP 200 farmers was 86.59% (dominant), with a difference in contribution of 16.42%, (3) Based on the Decent Living Needs (KHL) indicator, there were 21 families (70%) of IP 100 farmers and 22 families (73.5%) of IP 200 farmers. The t-test results show a significant difference between the welfare levels of farmers with an IP of 100 and an IP of 200, with the welfare levels of farmers with an IP of 200 being higher than those with an IP of 100.